Model of Character Education Based on Ubudiyah Muamalah in Madrasah Aliyah Darul Falah Pati - Muhlisin, Muhlisin; Ekosiswoyo, Rasdi; Rahman, Maman; Sugiyo, Sugiyo (The Journal of Educational Development, 2019)
This study aims to make the ubudiyah muamalah character education model effective. The ubudiyah muamalah character education is in accordance with the development in the madrasah. This research uses the research and development (R & D) approach which begins with finding the problem of character education, then proceeding to explore the results of research and development that are relevant to the problems being studied and then analyze them. The data source of this study consisted of ten papers that were presented in the seminar and five research papers. The data were analyzed using qualitative descriptive models. The results of the analysis show that the character education model for Islamic students consists of, among others, familiarity, educator modeling, scheduling, discipline, and continuous mentoring in competency planning, textbooks, learning manuals, and assessment instruments. The implementation of the ubudiyah muamalah character education model includes the role of educators, education staff, parents of students, the environment of students who are important factors. The evaluation system is good, objective, measurable, and authentic. The assessment from external institutions becomes a decisive part. This ubudiyah muamalah character education model will be better if it involves the role of religious leaders. Based on the results of the assessment carried out during one year of study it can be concluded that the development of the management model of the ubudiyah muamalah-based character education in Darul Falah Pati Aliyah madrasas can be carried out with good results.